Hide Information Using Table with Floating-Point Numbers - Raha, A.; Kasto, Nadia; Saffo, Dunia (Iraqi Journal of Science, 2025)
We present in this paper the development and implementation of a newsteganographic method, the information will be hidden in the selected parts of thetable with floating-point numbers used as stego cover. The method is implementedby transform each character in the text into numbers, then stores it as part of thefloating-point number. The main goal of steganography was fulfilled since theresulted table did not drown any suspicion, the same table can be used byexperimental person for the different calculation.